Орчин цагийн солонгос хэлийг монгол, турк хэлтэй харьцуулсан судалгаа: Comparative Research that Modern Korean Language with Mongolian and Turkish Languages - Yoon Seo, Choi (Mongolian Journal of Foreign Languages and Cultures, 2023)
Scientist G.I Ramstedt first suggests that the Korean language add to The Altaic language group in 1928, and proposed to add the Korean language to the Altaic language in 1934. But he began to doubt his first suggestion in 1950. To determine the origin and typology of a language, it is necessary to compare it with other languages. Therefore, in order to clarify the doubts of G.I. Ramstedt, I studied the Korean language from a modern point of view, comparing not only one, but also two languages which are Mongolian and Turkish, and tried to identify their similarities and differences. In addition, transitive verbs are inevitably related to vocative, so the distinction between vocative along transitive verbs is reflected in this research. Therefore, the meaning of my research lies in identifying the similarities and differences between the verbs of the three languages and deciphering their meanings.